Clinical survey over the past 35 years at the clinic for maxillofacial prosthetics Tokyo Medical and Dental University. Issue 3 (July 2018) - Yanagi, Ayaka; Sumita, Yuka; Hattori, Mariko; Kamiyanagi, Ayuko; Otomaru, Takafumi; Kanazaki, Ayako; Haraguchi, Mihoko; Murase, Mai; Hatano, Noriko; Taniguchi, Hisashi
Abstract: Purpose: The purpose of this survey was to examine the overview of maxillofacial prosthetic treatment at our department, in order to ascertain the actual status of patients and discuss future needs. Methods: Subjects were all patients who visited Clinic for Maxillofacial Prosthetics, Dental Hospital, Tokyo Medical and Dental University (TMDU) in the period from January 1, 1980 to December 31, 2014. Using medical records of the Clinic for Maxillofacial Prosthetics, Dental Hospital, TMDU, patients' data including sex, address, referring institution, and primary condition were analyzed throughout the period. Results: The number of patients over 35 years was 6219, with a man-to-woman ratio of 6:4. The number of patients in their 60s, 70s, and 80s showed an increasing trend. Patients with tumors accounted for about 50 % of cases in 1980–1984 and increased to 80 % in 2010–2014. Conclusions: The survey showed an increasing number of elderly patients and patients with tumors. This suggests that more awareness and education about maxillofacial prosthetics are needed.